2008
DOI: 10.1016/j.molcel.2008.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Activation Pathways Confer Cyclin-Binding Specificity on Cdk1 and Cdk2 in Human Cells

Abstract: Summary In metazoans, different cyclin-dependent kinases (CDKs) bind preferred cyclin partners to coordinate cell division. Here we investigate these preferences in human cells, and show that cyclin A assembles with Cdk1 only after complex formation with Cdk2 reaches a plateau, in late S and G2 phases. To understand the basis for Cdk2’s competitive advantage despite Cdk1’s greater abundance, we dissect their activation pathways by chemical genetics. Cdk1 and Cdk2 are activated by kinetically distinct mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(161 citation statements)
references
References 40 publications
15
145
0
1
Order By: Relevance
“…S2 A). These results are consistent with the recent report that cyclin A2 starts to form a complex with Cdk1 at mid-S phase (21). Cyclin A2-Cdk1 activity was detected earlier and enhanced in Chk1 del/Ϫ MEFs when compared with Chk1 lox/Ϫ MEFs (Fig.…”
Section: Chk1 Depletion Results In An Aberrant Origin Firing and A Hysupporting
confidence: 93%
See 1 more Smart Citation
“…S2 A). These results are consistent with the recent report that cyclin A2 starts to form a complex with Cdk1 at mid-S phase (21). Cyclin A2-Cdk1 activity was detected earlier and enhanced in Chk1 del/Ϫ MEFs when compared with Chk1 lox/Ϫ MEFs (Fig.…”
Section: Chk1 Depletion Results In An Aberrant Origin Firing and A Hysupporting
confidence: 93%
“…S8), the origin activation program appeared to be regulated not only by induction of Cdks and their binding to prereplicative complex components, but also by alternative ways such as complex formation with cyclins or regulation of inhibitory phosphorylation of Cdks. In this regard, it was very recently reported that Cdk1 started to form a complex with cyclin A2 after cyclin A2-Cdk2 complexes reached a plateau in mid S phase (21). Taken together, our results suggest that cyclin A2-Cdk1 may regulate origin firing program through both its specific accessibility to late origins and regulation of Cdk1 activity at late S phase.…”
Section: Discussionsupporting
confidence: 75%
“…These results are consistent with those of a recent study using centrifugal cell elutriation which showed that cyclin A assembles with Cdk1 only after complex formation with Cdk2 reaches a plateau during late S and G2 phases (Merrick et al 2008). Importantly, cyclin A2-Cdk1 activity was detected earlier and was enhanced in Chk1 del/− MEFs.…”
Section: Chk1 But Not Chk2 Is a Regulator Of The Origin Firing Prograsupporting
confidence: 93%
“…In primary human tumors, CDK2 abundance is frequently found to be elevated severalfold, and its associated kinase activity may be elevated up to 40-fold compared with nontumorigenic tissues (4)(5)(6)(7)23). Both CDK2 AS and CDK2 WT MEFs expressed human protein ∼10-fold higher than endogenous mouse CDK2 (24) (Fig. S1 E and F).…”
Section: As Cdk2 Forms Active Complexes In Vitro and Can Be Selectivelymentioning
confidence: 98%